'An acceptable level of violence': a Brazilian translation and digital rehearsed reading of Christina Reid's My Name, Shall I Tell You My Name?. Issue 2 (3rd April 2022) - Fernandes, Alinne Balduino P.; Garcez, Matias Corbett
ABSTRACT: In this article, we examine the ways digital spaces have shaped and affected how we produce and consume theatre during the COVID-19 pandemic. The case study in question consists of a retrospective analysis of the translation into Brazilian Portuguese, rehearsal process, and live digital rehearsed reading via Google Meet of Northern Irish Christina Reid's play My Name, Shall I Tell You My Name? ([1989] 1997). By reflecting on how digital technologies have been used as creative tools in theatre-making, we consider how the medium itself has affected the reception of the play by a small contemporary Brazilian audience.